A PRACTICAL IMPLEMENTATION SCIENCE HEURISTIC FOR ORGANIZATIONAL READINESS: R = MC2. Issue 4 (April 2015) - Scaccia, Jonathan P.; Cook, Brittany S.; Lamont, Andrea; Wandersman, Abraham; Castellow, Jennifer; Katz, Jason; Beidas, Rinad S.
<x xml:space="preserve">Abstract</x> There are many challenges when an innovation (i.e., a program, process, or policy that is new to an organization) is actively introduced into an organization. One critical component for successful implementation is the organization's readiness for the innovation. In this article, we propose a practical implementation science heuristic, abbreviated as R = MC2. We propose that organizational readiness involves (a) the motivation to implement an innovation, (b) the general capacities of an organization, and (c) the innovation‐specific capacities needed for a particular innovation. Each of these components can be assessed independently and be used formatively. The heuristic can be used by organizations to assess readiness to implement and by training and technical assistance providers to help build organizational readiness. We present an illustration of the heuristic by showing how behavioral health organizations differ in readiness to implement a peer specialist initiative. Implications for research and practice of organizational readiness are discussed.